Pengaruh Reminiscence Therapy Terhadap Fungsi Kognitif Pada Lansia - Ani Kuswati; Taat Sumedi; Hartati Hartati (JURNAL KEPERAWATAN MERSI, 2020)
Aging process (aging process) is a natural process characterized by a decreasing or changing in physical, psychological and social conditions when elderly people is  interacting with others. Aging process can decrease cognitive people and develop dementia, declining cognitive and memory. Reminiscence therapy is one technique to recall people memory and remind something in the pastThe purpose of this study is to know the effect of reminiscence therapy with group therapy method towards cognitive function of elderly peopleThis method of this study is   quasy experimental with pre-posttest design. The population in this study is elderly in Panti Werda Catur Nugroho Banyumas . Respondents were selected by Simple random sampling. The number of respondent was. Mini Mental Status Exam (MMSE) was used to measure cognitive function of the elderly people before and after being given reminiscence therapy. Statistical analysis in this study was using Wilcoxon Sign Rank Test and Mann Whitney-U Test.The results showed that there was a significant effect of increasing cognitive function by applying reminiscence therapy on elderly people with p = 0,000 (α = 0,005) and the mean value of elderly cognitive function in the treatment group increased by 4,416.The conclusion in this research is reminiscence therapy with group therapy method (TAK) is one of therapy modality that can improve cognitive function in elderly.